Local Passive Acoustic Monitoring of Narwhal Presence in the Canadian Arctic: A Pilot Project - Marcoux, Marianne; Auger-Méthé, Marie; Chmelnitsky, Elly G.; Ferguson, Steven H.; Humphries, Murray M. (ARCTIC, 2011)
Long-term community-based monitoring of narwhals (Monodon monoceros) is needed because narwhals are important to local Inuit and are facing changes in their environment. We examined the suitability of passive acoustic recording for monitoring narwhals, using data gathered in the Canadian Arctic from an autonomous acoustic recorder (Repulse Bay, 2006) and a hand-held digital recorder (Koluktoo Bay, 2006 – 08). We found a relationship between the number of narwhals observed passing a fixed point and the number of calls heard. In addition, we found that an automated call detector could isolate segments of recording containing narwhal vocalizations over long recording periods containing non-target sound, thus decreasing the time spent on the analysis. Collectively, these results suggest that combining passive acoustic sampling with an automated call detector offers a useful approach for local monitoring of the presence and relative abundance of narwhals. La nécessité d’avoir un programme communautaire de surveillance à long terme des narvals (Monodon monoceros) s’avère évidente étant donné que les narvals revêtent de l’importance aux yeux des Inuits de la région et que leur environnement est en pleine évolution. Nous explorons la pertinence d’un programme de surveillance par acoustique passive pour les populations de narvals à partir de données récoltées dans l’Arctique canadien à l’aide d’une enregistreuse autonome (Repulse Bay, 2006) et d’une enregistreuse portable (Koluktoo Bay, 2006 – 2008). Grâce à des enregistrements accompagnés d’observations sur le terrain, nous avons trouvé une corrélation entre le nombre de vocalisations entendues et le nombre de narvals observés. L’utilisation d’un détecteur automatique de vocalisations de narvals a permis d’isoler des segments d’enregistrements contenant des vocalisations de narvals sur de longues périodes d’enregistrement contenant des sons non-ciblés, et ainsi diminuer le temps d’analyse. Ces résultats suggèrent que la combinaison de surveillance acoustique ...